Flashback - Messenger, Shannon (Messenger, Shannon. Keeper of the lost cities, 2019)
Sophie Foster doesn't know whom to believe, and the Neverseen prove that she is vulnerable to attack. Sophie hopes to augment her powerful abilities with battle training so she can fight back. Meanwhile, another friend faces a different battle that forces Sophie and her friends to take a big risk--and that's just the distraction her enemies need to gain the upper hand.